2020
DOI: 10.1111/ans.15782
|View full text |Cite
|
Sign up to set email alerts
|

Sydney Facial Nerve Clinic: experience of a multidisciplinary team

Abstract: Background: The Sydney Facial Nerve Clinic (SFNC) is a multidisciplinary clinic established in 2015, consisting of surgeons (otolaryngologists, head and neck and plastics/ reconstructive), physiotherapists and speech pathologists. Methods: We reviewed patients who attended the SFNC in the first 3 years and who had their symptoms recorded using the Facial Disability Index, and clinical staging recorded utilising the House-Brackmann (HB) score, Sydney Facial Nerve Score and Sunnybrook Facial Grading System (SFGS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Treatment was most commonly directed to eye problems (66% of the cases) with only 20% of the participants receiving surgical therapies. Even within the subset of patients who have surgery, procedures to eyelids are reported to be the most common 15,60,65,67 . A retrospective review of patients treated with periocular procedures at John Hopkins Hospital in 2015 showed that lid loading was by far the most commonly used surgical procedure (95 out of 101 cases) 19 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Treatment was most commonly directed to eye problems (66% of the cases) with only 20% of the participants receiving surgical therapies. Even within the subset of patients who have surgery, procedures to eyelids are reported to be the most common 15,60,65,67 . A retrospective review of patients treated with periocular procedures at John Hopkins Hospital in 2015 showed that lid loading was by far the most commonly used surgical procedure (95 out of 101 cases) 19 .…”
Section: Resultsmentioning
confidence: 99%
“…64 In clinical practice a wide range of services are accessed by patients with FNP for the spectrum of problems they face. 15,65 Although most patients are managed non-operatively, it is not clear how much of this is simply due to lack of effective surgical solutions. 65 Szczepura et al carried out a national survey of 215 participants with FNP about their experience of treatment pathways.…”
Section: Interventions Accessedmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior to any intervention, it is important to consider which modality best suits the patient based on factors such as etiology, location of injury, patient age, life expectancy, psychological state, patient choice, existent comorbidities, sensory function of the trigeminal nerve, and oncological status. 37,57 In traumatic injury, availability of the proximal stump and extent of the facial nerve lesion are also important considerations. 58 Although differences in opinion do exist, in cases where the facial nerve remains anatomically intact, it is advisable allow a 12-month window prior to performing a procedure that will disrupt nerve integrity, to allow time for spontaneous recovery to occur.…”
Section: Surgical Reanimationmentioning
confidence: 99%